Divided : Why We're Living In An Age of Walls - Marshall, Tim (London Eliot & Thompson, 2018)
We feel more divided than ever. This riveting popular analysis tells you why.
Include Index and Bibliogrpahy
Keywords: Nationalism -- World politics -- Identity politics